2014
DOI: 10.1177/0269881114531666
|View full text |Cite
|
Sign up to set email alerts
|

Repeated lysergic acid diethylamide in an animal model of depression: Normalisation of learning behaviour and hippocampal serotonin 5-HT2 signalling

Abstract: A re-balance of postsynaptic serotonin (5-HT) receptor signalling, with an increase in 5-HT1A and a decrease in 5-HT2A signalling, is a final common pathway multiple antidepressants share. Given that the 5-HT1A/2A agonist lysergic acid diethylamide (LSD), when repeatedly applied, selectively downregulates 5-HT2A, but not 5-HT1A receptors, one might expect LSD to similarly re-balance the postsynaptic 5-HT signalling. Challenging this idea, we use an animal model of depression specifically responding to repeated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
40
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 60 publications
(46 citation statements)
references
References 63 publications
(79 reference statements)
3
40
0
Order By: Relevance
“…This finding was similar to an earlier article in which Grecksch et al, (1997) found reversal of these deficits by imipramine; Buchborn et al (2014) conclude that LSD has an antidepressant-like effect in this model.…”
Section: Nicholssupporting
confidence: 92%
See 1 more Smart Citation
“…This finding was similar to an earlier article in which Grecksch et al, (1997) found reversal of these deficits by imipramine; Buchborn et al (2014) conclude that LSD has an antidepressant-like effect in this model.…”
Section: Nicholssupporting
confidence: 92%
“…Using olfactory bulbectomy in rats as an animal model of depression, Buchborn et al (2014) demonstrated that repeated LSD treatment reversed the marked deficits in active avoidance learning in this animal model. This finding was similar to an earlier article in which Grecksch et al, (1997) found reversal of these deficits by imipramine; Buchborn et al (2014) conclude that LSD has an antidepressant-like effect in this model.…”
Section: Nicholsmentioning
confidence: 96%
“…In the former, a single dose immediately after learning enhanced memory consolidation in adult mice, while treatment immediately before learning facilitated the extinction of fear memory (21). In the latter, chronic treatment of adult rats with d-LSD for 11 days improved learning in animals deprived of olfaction by bulbectomy, but no effects were observed in sham controls (22). The lesion increases hippocampal 5-HT2A levels, and d-LSD down-regulated these to normal levels, with no effects in sham animals.…”
Section: Introductionmentioning
confidence: 97%
“…These substances have also been shown to induce neural plasticity and synaptogenesis both in vitro and in vivo (18)(19)(20), and are therefore likely to enhance learning capacity. Indeed, psychedelics have been shown to enhance memory consolidation when administered after fear learning or novel object exploration (21,22). In the former, a single dose immediately after learning enhanced memory consolidation in adult mice, while treatment immediately before learning facilitated the extinction of fear memory (21).…”
Section: Introductionmentioning
confidence: 99%
“…By expanding the reality cone and promoting conceptual overlap, the high entropy state facilitates creativity, novel thinking, and imagination, which are obviously of great importance in human cognition. Furthermore, psychedelics are beginning to show great promise as psychotherapeutic agents in the treatment of depression, anxiety, and obsessive compulsive disorder (Moreno and Delgado, 1997; Berman et al, 2000; aan het Rot et al, 2010; Buchborn et al, 2014), perhaps by allowing sufferers to break out of the inflexible and circular modes of thinking that characterize these conditions (Carhart-Harris et al, 2014). …”
Section: The Psychedelic State and Iitmentioning
confidence: 99%